EFEKTIVITAS PENDEKATAN OPEN ENDED DALAM PEMBELAJARAN JARAK JAUH DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - Hesti Noviyana; Fitriana Rahmawati; Nella Findriani (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2021)
Mathematical critical thinking ability is one of the objectives of learning mathematics. This ability is a provision for students in dealing with problems. The importance of this ability is not in line with the abilities of junior high school students in the current distance learning conditions, for this reason this study examines the effectiveness of the Open Ended approach in terms of the mathematical critical thinking abilities of eighth grade students in odd semesters of SMP Negeri 13 Bandar Lampung in the 2021/2022 academic year. This research is a quasi-experimental research, with a population of all students of class VIII Odd Semester SMP Negeri 13 Bandar Lampung. The sample of 2 classes, namely class VIII 1 as the experimental class, and class VIII 3 as the control class, were taken using the Cluster Random Sampling technique. Students' mathematical critical thinking ability is measured by a test in the form of an essay as many as 5 questions which have been tested for validity and reliability. The results of hypothesis testing show the value of thitung = 7.35. From the t distribution table at a significant level of 5%, it is known that ttabel = t(1-α) = 1.67. This means that thitung > ttabel, so it can be concluded that the application of the Open Ended approach is effective in terms of the mathematical critical thinking skills of class VIII students in the odd semester of SMP Negeri 13 Bandar Lampung in the 2021/2022 academic year.